2019
DOI: 10.3390/biom9100627
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sterols on the Interaction of SDS, Benzalkonium Chloride, and A Novel Compound, Kor105, with Membranes

Abstract: Sterols change the biophysical properties of lipid membranes. Here, we analyzed how sterols affect the activity of widely used antimicrobial membrane-active compounds, sodium dodecyl sulfate (SDS) and benzalkonium chloride (BAC). We also tested a novel benzalkonium-like substance, Kor105. Our data suggest that benzalkonium and Kor105 disturb the ordering of the membrane lipid packaging, and this disturbance is dampened by cholesterol. The disturbance induced by Kor105 is stronger than that induced by BAC becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…To address this issue experimentally, we synthesized the corresponding molecules, and keeping in mind that phosphor-organic compounds are generally not recommended for the use on humans, the novel molecules contain nitrogen instead of phosphorus ( Figure 5 A). While the compound with one phenyl group, Kor105, has recently been described by us as a potential surfactant [ 19 ], FS1 is a novel substance. As shown by Figure 4 , both compounds stimulated cell growth, with FS1 having a wider range of acting concentrations than Kor105 or C 12 TPP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To address this issue experimentally, we synthesized the corresponding molecules, and keeping in mind that phosphor-organic compounds are generally not recommended for the use on humans, the novel molecules contain nitrogen instead of phosphorus ( Figure 5 A). While the compound with one phenyl group, Kor105, has recently been described by us as a potential surfactant [ 19 ], FS1 is a novel substance. As shown by Figure 4 , both compounds stimulated cell growth, with FS1 having a wider range of acting concentrations than Kor105 or C 12 TPP.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, it is possible that the rescuing effect of BAC, as well as the rescuing effects of C 12 TPP, FS1 and Kor105, was due to its action on the plasma membrane (PM). Recently, we have shown that mutants with elevated levels of plasma membrane ergosterol are more resistant to Kor105 and C 12 TPP than the wild type [ 19 ]. Similar to that of the other two substances, the toxicity of FS1 was also found to be lower in the mutant with elevated PM ergosterol ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of electrical field on membrane deformation was observed, in part, by the method of inner field compensation on the bilayer membranes. Its application showed a change in the membrane thickness and capacitance when the membrane interacts with various compounds [ 85 , 86 , 87 ], including the membrane-bound proton fraction [ 3 , 4 ]. We proposed that a similar effect may also present in the MIM under proton pump functioning [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first one, the inner field compensation (IFC) method, is based on the measurement of the second harmonics of the capacitive current ( [31]). In the second method, the change of ∆ϕ b is determined from the change of the BLM conductance induced by ionophore nonactin as [32][33][34][35]…”
Section: Experiments At Blmmentioning
confidence: 99%